Towards a realistic prediction of sintering of solid oxide fuel cell electrodes: From tomography to discrete element and kinetic Monte Carlo simulations. (15th March 2018) - Yan, Z.; Hara, S.; Shikazono, N.
Abstract: The 3-dimensional (3D) particle geometries in sub-micrometric La0.6 Sr0.4 Co0.2 Fe0.8 O3 − δ powder are obtained by high-resolution focused ion beam scanning electron microscope (FIB-SEM) tomography. Irregularly shaped particles are represented with volume equivalent single spheres (single-sphere model) or clumped multispheres (multi-sphere model), based on their 3D geometries. The discrete element method (DEM) is used to reproduce "virtual" powder packings with multi-sphere and single-sphere models. The DEM-generated virtual microstructures and the FIB-SEM real microstructures are submitted to kinetic Monte Carlo (KMC) simulations of sintering. It is shown that the multi-sphere model predicts more realistic microstructure than the single-sphere model for sintering of La0.6 Sr0.4 Co0.2 Fe0.8 O3 − δ . Graphical abstract: Image 2